2018
DOI: 10.1659/mrd-journal-d-16-00124.1
|View full text |Cite
|
Sign up to set email alerts
|

Local Residents' Perceptions of a Dam and Reservoir Project in the Teesta Basin, Darjeeling Himalayas, India

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…The key finding was that households felt that their access to economic opportunities in the post dam construction was negligible. The results of this research support the argument in the literature that the public approval of development project is usually combined with conditions, which the project proponent is supposed to meet (Obour et al, 2016;Wiejaczka et al, 2018). Obour et al (2016), for example found similar experiences in the post Bui Dam construction in Ghana, with respondents arguing that the dam had led to increased poverty, food insecurity, health problems and property loss amongst people living in the catchment area.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The key finding was that households felt that their access to economic opportunities in the post dam construction was negligible. The results of this research support the argument in the literature that the public approval of development project is usually combined with conditions, which the project proponent is supposed to meet (Obour et al, 2016;Wiejaczka et al, 2018). Obour et al (2016), for example found similar experiences in the post Bui Dam construction in Ghana, with respondents arguing that the dam had led to increased poverty, food insecurity, health problems and property loss amongst people living in the catchment area.…”
Section: Discussionsupporting
confidence: 79%
“…One frequently mentioned reason for local communities' opposition to dam projects is insufficient compensation (Wiejaczka et al, 2018). In this study, those who received cash compensation considered the once off cash payments inadequate to make up for loss of their livelihood resources such as grazing pastures.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the river channels above dams there is an intense accumulation of sediments, while below due to erosion there is a degradation of and dredging of the riverbed [23,24,25]. The Teesta river transports a large number of sediments, exploited in many places by local communities after the flood period [26]. The damming of the river will block the fluvial transport in the river and because of intensive accumulation within the channel and flood plain of the river will cause rapid shallowing of the river channel and the reservoirs.…”
Section: Human Interference In the Morphology Of Himalayan Riversmentioning
confidence: 99%
“…Faggi et al (2013) conducted one of the few studies to examine evaluations of ''water landscapes'' by residents of and visitors to a place, in this case, natural areas with water features in metropolitan Buenos Aires (Argentina). Aquatic ecosystems in mountain areas are particularly understudied, aside from a recent study by Wiejaczka et al (2018) that analyzed residents' perceptions of a proposed dam and reservoir in the Indian Himalayas.…”
Section: Introductionmentioning
confidence: 99%